2005
DOI: 10.1007/s10620-005-2761-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 1-Week Helicobacter pylori Eradication Therapy with Rabeprazole, Clarithromycin, and Metronidazole on 13C-Aminopyrine Breath Test

Abstract: Helicobacter pylori eradication therapy is commonly prescribed in the general population. Treatment consists of drugs that are mainly metabolized by the liver cytochrome P-450 (CYP) enzymatic pool. Most H. pylori-infected patients often take drugs for comorbid illnesses, therefore increasing the potential for drug-drug interactions. We aimed to evaluate the interactions of rabeprazole, clarithromycin, and metronidazole 1-week H. pylori eradication therapy with CYP-dependent liver metabolic function in clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…We have shown that 13 C-ABT can be used to evaluate the modification of CYP activity during Helicobacter pylori eradication therapy with various PPIs, metronidazole, and clarithromycin [7,33]. In one of these studies we found that rabeprazole seems to display less interaction with CYP activity than other PPIs [7]. The results of the current study further strengthen those of our previous study and underscore the safety profile of rabeprazole.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We have shown that 13 C-ABT can be used to evaluate the modification of CYP activity during Helicobacter pylori eradication therapy with various PPIs, metronidazole, and clarithromycin [7,33]. In one of these studies we found that rabeprazole seems to display less interaction with CYP activity than other PPIs [7]. The results of the current study further strengthen those of our previous study and underscore the safety profile of rabeprazole.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, previous studies have shown that 13 C-ABT can be used as a tool to identify the influence of oral contraceptives, grapefruit juice, and alcohol on liver CYP enzymatic activity [12,13]. We have shown that 13 C-ABT can be used to evaluate the modification of CYP activity during Helicobacter pylori eradication therapy with various PPIs, metronidazole, and clarithromycin [7,33]. In one of these studies we found that rabeprazole seems to display less interaction with CYP activity than other PPIs [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the peculiar pharmacokinetics and pharmacodynamics of rabeprazole allow a faster onset of action, and more rapid inhibition of proton pumps than other PPIs, 32, 33 thus making this drug more suitable for short‐term eradication treatment because both fast activation and rapid onset of gastric acid suppression are especially needed in short‐term therapy. Moreover, rabeprazole has relevant in vitro antimicrobial activity, 34, 35 and its administration does not seem to interfere with cytochrome P‐450 activity 36, 37 . This is especially important as in this study, and as happens in everyday clinical practice, approximately half of the patients were on co‐medication, and in this setting the occurrence of drug–drug interactions is more likely.…”
Section: Discussionmentioning
confidence: 58%
“…Clinically, clarithromycin is commonly prescribed in combination with rabeprazole or other antibiotics to eliminate H. pylori. 1 The present case reports the appearance of a dissociative disorder in a woman taking clarithromycin in combination with rabeprazole. The study was approved by the Ethics Committee of The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, China.…”
Section: Introductionmentioning
confidence: 80%